Your Last Purchase but Chosen Not by You: How Buyers Make Their Choices in the Market for Funeral Services - МоисееваЕкатерина Николаевна (Journal of Economic Sociology, 2013)
The article is devoted to consumer choice-making in markets of funeral services, influence of social networks on market transactions, and role of emotions in the indicated processes. Choice-making in markets of funeral services is considered in terms of social interaction. Physical death of an individual is not supposed to result in eliminating his (her) social roles. Social role is well known to be generated from social interactions and social situations. Thus, even after his (her) death an individual may be involved into social interactions affecting decisions taken by his (her) family members. Choosing certain goods and services, relatives demonstrate their attitude towards the dead person, and funeral agencies may turn out to have a success in profit seeking. According to Viviana Zelizer, people don’t stop differentiating significant social relations, performing any economic actions. In markets of funeral services the patterns of prevalent (though not the only ones) social relations include gift-making, i.e. consumers interpret the way how funerals are organized and conducted in terms of gifting. Gift’s appropriateness and funeral’s “worthy” expressed in a specific sum of money, are generally determined by the fact how family members value the dead person. The paper is built upon the research carried out in Moscow and Saint-Petersburg in 2009–2011 and in Massachusetts (US) in 2011–2012.